Dispensasi Nikah dalam Pernikahan Anak Perspektif Hukum dan Sosiologi - Surasa, Ais; Mukhlas, Oyo Sunaryo; Saebani, Beni Ahmad; Husain, Husain (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The rise of the phenomenon of early marriage in Indonesia is the background to the birth of Republic of Indonesia Law number 16 of 2019 concerning marriage and the compilation of Islamic law, which sets the age limit for marriage to 19 years. The reality is that in society there are many cases asking to be able to get married and have it officially registered, which has led to the existence of a marriage dispensation. Marriage dispensation is permitted by law by considering positive matters. The aim of this study is to determine the long-term impact of early marriage on the welfare of individuals, families and society. The method used is qualitative, data collection is carried out by interviews, direct observation and also data related to the theme. Using this method will make it easier to observe phenomena in society regarding marriage dispensations. The data analysis used was an inductive method (Creswell, 1994). The results obtained were that the marriage dispensation from a legal perspective did not conflict with Law 16 of 2019. The granting of marriage dispensations was carried out by considering the impact. From a sociological perspective, our society views early marriage as something normal and often forgets the impact of child marriage. Marriage dispensation is a rational choice, even though the risks faced are very high. Therefore, it is necessary to increase public awareness of promiscuity and return to the essence of marriage.